A multi-method approach to circular strategy design: Assessing extended producer responsibility scenarios through material flow analysis of PET plastic in Jakarta, Indonesia. (20th September 2022) - Amin, Samir; Strik, David; van Leeuwen, Judith
Highlights: Circular policies need to be aligned to circular and sustainability goals. Circular policies should build upon pros and cons of a current linear system. Assessment and scenario methods can be combined to inform circular policies. Extended Producer Responsibility for PET plastic in Jakarta should be collective. Extended producer responsibility should build on informal sector in waste management.